Bio-nanotechnology application in wastewater treatment - Saleh Habtoor, Salah; Agam, Mohd Arif; Al-Gheethi, Adel; Radin Mohamed, Radin Maya Saphira; Noman, Efaq (Springer Nature, 2020)
The nanoparticles have received high interest in the ﬁeld of medicine and water puriﬁcation, however, the nanomaterials produced by chemical and physical methods are considered hazardous, expensive, and leave behind harmful substances to the environment. This chapter aimed to focus on green-synthesized nanoparticles and their medical applications. Moreover, the chapter highlighted the applicability of the metallic nanoparticles (MNPs) in the inactivation of microbial cells due to their high surface and small particle size. Modifying nanomaterials produced by green-methods is safe, inexpensive, and easy. Therefore, the control and modiﬁcation of nanoparticles and their properties were also discussed.